USER INTERFACE DESAIN WEBSITE CV. EKOKAPTI CREATIVE PRODUCTION - Farid; Khoirul Anwar, Ahmad (JURNAL KEMADHA, 2025)
The development of information technology in Indonesia facilitates access to information and communication, both domestically and abroad. The existence of a functional and attractive website is an essential element in the marketing and operational strategies of various companies such as the broadcasting industry and media production. The website functions not only as an information medium but also as a tool to strengthen the brand and build relationships with clients. The creative industry in Surakarta has great potential to develop due to its rich culture and creative human resources. The website design process for Cv. Ekokapti Creative Production is structured through the stages of Idea/Concept, Observation, Brief, Brainstorming, Creative Brief, Design, and Evaluation. The resulting website has a responsive, user- friendly appearance and displays service information clearly and attractively. Design elements such as portfolio galleries, interactive videos, and intuitive navigation are applied to enhance visual appeal and user experience. With an aesthetic and functional concept, this website is not only a means of promotion but also strengthens the brand identity of Cv. Ekokapti Creative Production in the creative industry. Keywords: Design, Website, Branding, Promotion, Creative Industry